Arbuscular mycorrhizal fungi in saline soils: Vertical distribution at different soil depth - Becerra, Alejandra Gabriela (2014)
Arbuscular mycorrhizal fungi (AMF) colonize land plants in every ecosystem, even extreme conditions such as saline soils. In the present work we report for the first time the mycorrhizal status and the vertical fungal distribution of AMF spores present in the rhizospheric soil samples of four species of Chenopodiaceae (Allenrolfea patagonica, Atriplex argentina, Heterostachys ritteriana and Suaeda divaricata) at five different depths in two saline of central Argentina. Roots showed medium, low or no colonization (0-50%). Nineteen morphologically distinctive AMF species were recovered. The number of AMF spores ranged between 3 and 1162 per 100 g dry soil, and AMF spore number decreased as depth increased at both sites. The highest spore number was recorded in the upper soil depth (0-10 cm) and in S. divaricata. Depending of the host plant, some AMF species sporulated mainly in the deep soil layers (Glomus magnicaule in Allenrolfea patagonica, Septoglomus aff. constrictum in Atriplex argentina), others mainly in the top layers (G. brohultti in Atriplex argentina and Septoglomus aff. constrictum in Allenrolfea patagonica). Although the low percentages of colonization or lack of it, our results show a moderate diversity of AMF associated to the species of Chenopodiaceae investigated in this study. The taxonomical diversity reveals that AMF are adapted to extreme environmental conditions from saline soils of central Argentina.